2023
DOI: 10.1038/s41467-022-35778-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of PRMT5 in chronic lymphocytic leukemia promotes progression with high risk of Richter’s transformation

Abstract: Richter’s Transformation (RT) is a poorly understood and fatal progression of chronic lymphocytic leukemia (CLL) manifesting histologically as diffuse large B-cell lymphoma. Protein arginine methyltransferase 5 (PRMT5) is implicated in lymphomagenesis, but its role in CLL or RT progression is unknown. We demonstrate herein that tumors uniformly overexpress PRMT5 in patients with progression to RT. Furthermore, mice with B-specific overexpression of hPRMT5 develop a B-lymphoid expansion with increased risk of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…In vitro anti-MCL activity was demonstrated in 9 cell lines, which showed IC50s ranging from 44.8 to 1905.5 nM, with the maximal effect occurring on day 9 ( Figure 1 A; supplemental Figure 1 B). This compound was found to be more potent than EPZ015666 (GSK3235025), a well-described PRMT5 inhibitor 58 ( supplemental Figure 1 C). In vivo, PRT382 demonstrated a favorable oral bioavailability and pharmacokinetic profile in mice (area under curve, 1175 h∗kg∗ng/mL per mg at 10 mg/kg) ( supplemental Figure 1 D).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In vitro anti-MCL activity was demonstrated in 9 cell lines, which showed IC50s ranging from 44.8 to 1905.5 nM, with the maximal effect occurring on day 9 ( Figure 1 A; supplemental Figure 1 B). This compound was found to be more potent than EPZ015666 (GSK3235025), a well-described PRMT5 inhibitor 58 ( supplemental Figure 1 C). In vivo, PRT382 demonstrated a favorable oral bioavailability and pharmacokinetic profile in mice (area under curve, 1175 h∗kg∗ng/mL per mg at 10 mg/kg) ( supplemental Figure 1 D).…”
Section: Resultsmentioning
confidence: 92%
“…To selectively target PRMT5 activity in MCL, we used PRT382 (Prelude Therapeutics), a novel S-adenosyl methionine competitive, selective small-molecule inhibitor of PRMT5 enzymatic activity 58 ( supplemental Figure 1 A). In vitro anti-MCL activity was demonstrated in 9 cell lines, which showed IC50s ranging from 44.8 to 1905.5 nM, with the maximal effect occurring on day 9 ( Figure 1 A; supplemental Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanisms driving the pathogenesis and progression of CLL have not been fully elucidated. A subset of patients experience an aggressive disease course in the absence of known high-risk genetic alterations, which indicates that there are still many undiscovered factors promoting the progression of CLL [ 20 ]. For example, Hortal et al recently identified that the overexpression of the wild type oncogene RRAS2 is behind the development of CLL, the most frequent leukemia in the western world [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study utilizing scRNA-seq on spleen- and LN-derived CLL cells from Eμ-TCL1 Akt-C mice in a model of RT pointed to the importance of sustained Akt signaling for maintaining a pro-proliferative and anti-apoptotic microenvironment through aberrant NOTCH1 activation ( 115 ). scRNA-seq was also instrumental in identifying the epigenetic modifier PRMT5 as a potential mediator of RT, in patient tissues as well as in an experimental model employing Eμ-PRMT5/TCL1 mice ( 116 ).…”
Section: Deciphering Clonal Heterogeneity and Evolution In Cllmentioning
confidence: 99%